The Impact of Fiscal Policy Variables on Output Growth - Gerson, Philip (IMF Working Papers; Working Paper, 1998)
This paper surveys the theoretical and empirical literature on the relationship between taxation and public expenditure and economic growth. Particular attention is paid to the effect of taxation and government expenditure on the supply and productivity of labor and physical capital. Studies suggest that well-targeted government expenditures on health, education, and infrastructure should have a positive impact on growth. By contrast, the impact of taxation on the supplies of labor and capital, and on output growth, is more muted.